Healthy Minds, Healthy Bodies: Enhancing Physical Health in Serious Mental Illness – BSW (Bath, Swindon and Wiltshire) Physical Health Evaluation - Elizabeth Ewins; Ian Burgess; Alison Kinge; Josephine Raffan-Burnett (BJPsych Open)
Aims: The BSW (Bath, Swindon and Wiltshire) Community Physical Health Evaluation aimed to assess the implementation and outcomes of annual physical health checks for individuals with Serious Mental Illness (SMI) within the BSW region. BSW offer an assertive outreach approach for physical health checks by mental health specific nurses and support workers. The evaluation explored compliance with physical health check processes, follow-up practices for abnormal results, and the role of social deprivation in influencing health check uptake. It sought to identify barriers, assess adherence to policy guidelines, and recommend improvements for managing cardio-metabolic risk.